AtDGAT2 is a functional acyl‐CoA:diacylglycerol acyltransferase and displays different acyl‐CoA substrate preferences than AtDGAT1. Issue 15 (13th June 2013) - Zhou, Xue-Rong; Shrestha, Pushkar; Yin, Fang; Petrie, James R.; Singh, Surinder P.
Abstract : Demonstration of the function of the Arabidopsis thaliana acyl‐CoA:diacylglycerol acyltransferase 2 (AtDGAT2) has remained elusive despite biochemical testing of genetic mutants and overexpression lines. We show that transiently expressed AtDGAT2 in the Nicotiana benthamiana leaf resulted in an increase in triacylglycerol twice as great as the increase observed following parallel expression of AtDGAT1. AtDGAT2 showed higher conversion from labeled diacylglycerol to triacylglycerol compared to AtDGAT1, and was acyl‐CoA dependent. In addition, AtDGAT2 had different acyl‐CoA substrate preference than AtDGAT1. These results allow us to conclude that AtDAGT2 is a functional acyl‐CoA:diacylglycerol acyltransferase enzyme that can catalyse substantial increase in TAG synthesis. Abstract : AtDGAT2 is confirmed as a functional acyl‐CoA dependent acyl‐CoA:diacylglycerol acyltransferase. Expression of AtDGAT2 results in higher TAG accumulation in leaf than AtDGAT1. AtDGAT2 shows higher DAG to TAG conversion rate than AtDGAT1. AtDGAT2 displays different substrate preference than AtDGAT1.